THEATER AS A PEDAGOGICAL TOOL TO TEACH HISTORY OF CONTEMPORARY EDUCATION - Álvarez Domínguez, Pablo (2016)
If current universities demand an education that trains individuals to face future changes, now we face the challenge to educate for change. Innovation, creativity and theater as art are fundamental pillars for a more revealing construction of historical and educational knowledge. From this approach, we can provide justification for a more practical and significant teaching of History of Education, based on the use of pedagogical resources that are more attractive for students. This paper presents the development of a teaching innovation in the History of Contemporary Education subject of the Degree Course on Pedagogy at the University of Seville, which results in the application and use of theater pedagogy as a teaching resource to learn about education in the past.